Empowering adult learners through information literacy: a case study on using MIT app inventor in second chance schools - Tegousi Nafsika; Drakopoulos Vasileios (Discover Education)
Abstract This article presents a case study involving the use of a Free and Open-Source Software programming environment to teach a thematic unit within the Information Literacy curriculum for first-year adult learners at a Second Chance School in Greece. This study explores the implementation of a modern, hands-on teaching approach tailored to the unique needs of Second Chance School learners- adults who often face a range of academic and personal challenges. The selected programming environment provides a safe, engaging, and modern platform for learning, particularly through project-based instruction. Findings suggest that experiential, hands-on teaching methods are significantly more effective than traditional approaches, especially for learners who may struggle with conventional academic settings as well as those with limited prior tech experience. The article concludes with implications for educational management and suggestions for future research.